2022
DOI: 10.1039/d2ra05176a
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of oligostilbenes fromIris lacteaPall. var.chinensis(Fisch.) Koidz and their anti-inflammatory activities

Abstract: Oligostilbenes from Iris lactea Pall.var. chinensis (Fisch.) Koidz and their anti-inflammatory activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Liping et al [ 74 ] found Cr, Zn, Cu, Tl, Sb, and Cd in Malinzi by inductively coupled plasma-optical emission spectrometry (ICP-OES) with microwave digestion. Malinzi macerated with 5.0 % NaOH aqueous solution using the alkaline-acid method, and vitisin A-13- O -β- d -glucoside (31) was separated by the semi-preparative HPLC [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liping et al [ 74 ] found Cr, Zn, Cu, Tl, Sb, and Cd in Malinzi by inductively coupled plasma-optical emission spectrometry (ICP-OES) with microwave digestion. Malinzi macerated with 5.0 % NaOH aqueous solution using the alkaline-acid method, and vitisin A-13- O -β- d -glucoside (31) was separated by the semi-preparative HPLC [ 42 ].…”
Section: Introductionmentioning
confidence: 99%